Arsenic Cycling in Hydrocarbon Plumes: Secondary Effects of Natural Attenuation. Issue 1 (21st January 2015) - Cozzarelli, Isabelle M.; Schreiber, Madeline E.; Erickson, Melinda L.; Ziegler, Brady A.
Abstract: Monitored natural attenuation is widely applied as a remediation strategy at hydrocarbon spill sites. Natural attenuation relies on biodegradation of hydrocarbons coupled with reduction of electron acceptors, including solid phase ferric iron (Fe(III)). Because arsenic (As) adsorbs to Fe‐hydroxides, a potential secondary effect of natural attenuation of hydrocarbons coupled with Fe(III) reduction is a release of naturally occurring As to groundwater. At a crude‐oil‐contaminated aquifer near Bemidji, Minnesota, anaerobic biodegradation of hydrocarbons coupled to Fe(III) reduction has been well documented. We collected groundwater samples at the site annually from 2009 to 2013 to examine if As is released to groundwater and, if so, to document relationships between As and Fe inside and outside of the dissolved hydrocarbon plume. Arsenic concentrations in groundwater in the plume reached 230 µg/L, whereas groundwater outside the plume contained less than 5 µg/L As. Combined with previous data from the Bemidji site, our results suggest that (1) naturally occurring As is associated with Fe‐hydroxides present in the glacially derived aquifer sediments; (2) introduction of hydrocarbons results in reduction of Fe‐hydroxides, releasing As and Fe to groundwater; (3) at the leading edge of the plume, As and Fe are removed from groundwater and retained on sediments; and (4) downgradient from the plume, patterns of As and Fe in groundwater are similar to background. We develop a conceptual model of secondary As release due to natural attenuation of hydrocarbons that can be applied to other sites where an influx of biodegradable organic carbon promotes Fe(III) reduction.